Pengaruh Konsumsi Buah Kurma terhadap Kadar Hemoglobin Ibu Hamil dengan Anemia - Tri Restu Handayani; Lina Contesa (Jurnal Anestesi, 2024)
Globally, the prevalence of anemia in pregnant women in developed countries is 49% and in developing countries it is 53%. In Indonesia, the rate of anemia in pregnant women is quite high, namely 48.9%. Anemia in pregnant women can increase the risk of premature birth and bleeding. One effort that can help prevent and treat anemia in pregnant women is to consume foods that are sources of iron, for example dates. The aim of the research was to determine the effect of consuming dates on hemoglobin levels in pregnant women with anemia. The research design used a quasi-experimental one group with control group. The experimental group was the group that consumed dates and Fe tablets, while the control group only consumed Fe tablets. The population is all third trimester pregnant women at PMB Lina in May 2024, totaling 24 respondents where each group consists of 12 respondents. The sampling technique used is total sampling. Based on the results of the normality test, sig. >0.05, then the statistical test used is the Paired Sample T Test. The average hemoglobin level in the experimental group before being given dates and Fe tablets was 10.2 gr/dl and the average hemoglobin level after being given date palm juice was 11.4 gr/dl. The results of the Wilcoxon test obtained a p value of 0.001, meaning that there was an effect of giving dates on hemoglobin levels in pregnant women. It is hoped that health workers can increase public knowledge, especially pregnant women, about food sources high in iron so that they can prevent and reduce the incidence of pregnancy anemia. Key words: , ,